دراسة تأثير التقوية بوساطة الأربطة الفولاذية أو جدران القص على التجاوب الزلزالي لمبنى قائم من الخرسانة المسلحة - ناصر, عصام; حسن, نائل; محفوض, زيد (Latakia University Journal -Engineering Sciences Series, 2019)
يهدف هذا البحث لدراسة تأثير التقوية بواسطة الأربطة الفولاذية أو تحويل الإطارات إلى جدران قص على التجاوب الزلزالي لمبنى قائم من الخرسانة المسلحة (أي على قوة القص القاعدي الكلية التي يخضع لها هذا المبنى وعلى عزوم الانعطاف وقوى القص والانتقالات الخاصة بأعمدة هذا المبنى). كما جرى فيه إلقاء الضوء على العلاقة بين زيادة عدد الإطارات المقواة بكل من هذين الأسلوبين وفعالية هذين الأسلوبين في تخفيض عزوم الانعطاف وقوى القص والانتقالات الخاصة بأعمدة المبنى المدروس.أيضاً تتطرق البحث إلى تأثير انقطاع الأربطة الفولاذية وجدران القص في الطابق الأخير (لأسباب وظيفية) على قيم عزوم الانعطاف وقوى القص والانتقالات الخاصة بأعمدة هذا الطابق.بغية تحقيق الأهداف المذكورة أعلاه، تم إجراء تحليل زلزالي للمبنى في سبع حالات ( حالة المبنى غير المقوى، حالات المبنى المقوى بالأربطة في إطارين، أربع إطارات، ستة إطارات، وحالات المبنى المقوى بتحويل إطارين أو أربعة إطارات أو ستة إطارات إلى جدران قص)، وذلك بطريقة تراكب الأنماط وبالاستناد إلى طيف استجابة تصميمي.في نهاية الدراسة تبين أن انقطاع عناصر التقوية في الطابق الأخير، أدت إلى زيادة قيم عزوم الانعطاف وقوى القص والانتقالات الخاصة بأعمدة ذلك الطابق. بالنسبة لبقية الطوابق ترتب على تقوية المبنى انخفاض بمقدار %70 في قيم عزوم الانعطاف وقوى القص والانتقالات النسبية الخاصة بأعمدة تلك الطوابق. حيث لوحظ أن %50 من الانخفاض في قيم عزوم الانعطاف وقوى القص و%40 من الانخفاض في قيم الإنزياحات الطابقية ناتجة عن زيادة عدد الإطارات المقواة من أربعة إلى ستة. The purpose of this research is to study the effect of strengthening by steel braces or by transformation of the frames into shear walls on the seismic response of existing reinforced concrete building (in the other words, on the total base shear force of the building, bending moments, shear forces, and displacements of the columns of this building). In addition, this research deals with the relationship between the number of the strengthened frames and the efficiency of strengthening. Finally, this research deals with the effect of the discontinuity of the strengthening elements in the last storey on the values of bending moments, shear forces, and displacements of the columns of the last storey. To perform those purposes, seismic analysis of the building had been performed for seven cases (the case of the building without strengthening; the cases of the building strengthened by steel braces in two, four or six frames; the cases of the building strengthened by two, four or six shear walls).This analysis had performed by modal superposition method .At the end of this study, we find out that the discontinuity of strengthening elements in the last storey results in increase in the bending moments ,shear forces and displacements of the columns of the last storey. With respect to the other stories, the strengthening of the building results in decrease as much as 70% in the values of bending moments, shear forces and displacements of the columns of these stories .It is noteworthy that the greatest part of this decrease results from the increase in the number of the strengthening frames from four to six.